ACCESSIBILITY WITH RAPID PROTOTYPING FOR PEOPLE WITH VISUAL DISABILITIES (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
The university and society have been undergoing major changes in recent years. One is the speed with which technological innovations are developed and diffused, and it is fundamental for the university to create potential for the development of science and technology and to contribute to the training of students for this reality. In this context, strengthening the integration between teaching, research and extension is fundamental. This study aims to analyze the difficulties and needs of the visually impaired or of individuals with low vision, using rapid prototyping technology (3D printing) in order to reduce these difficulties. Our laboratory makes use of Molten Polymer Deposition (MPD) technology, also known as Fused Deposition Modeling (FDM) or FFF (Fused Filament Fabrication), in which a thermoplastic filament is forced through a heated extrusion nozzle. The machine is formed by a head which moves in the x and y axes, and a platform responsible for translate vertically. The material injector heats and pulls the plastic filament that gets rolled up in a coil. The material passes through an extruder nozzle located on the head to then be deposited on the platform. The laboratory contributes to the creation and development of a more personalized, fast and low cost of customized parts and products of materials for people with visual impairment. Using rapid prototyping technology, materials adapted to the visually impaired are being developed and created, favoring the fixation and facilitating detail discrimination through touch, taking into account the peculiarities of the visually impaired. In conjunction with other departments of Universidade Federal do Rio Grande (FURG), were already developed some products, as the Prototype of the central library tactile map of Carreiros Campus, some platelets with Adinkras in high relief, Braille cube, 3D printer with solar system model, Orion constellation with the Martian crater and a T7 human vertebra. The inclusion of people with visual impairment is something that is happening and opens up a vast field for the research and development of teaching in our country.